Assessment and resilience of Merapoh Trail, Gunung Tahan, Malaysia - Othman, Zainal Abidin (2022)
Gunung Tahan (2,187 metres above sea level) in Taman Negara National Park is one of Malaysia's ultimate trekking trails into the country's wilderness. The mountain top can be reached via two main trails: The Kuala Tahan Trail and the Merapoh Trail, with the latter receiving more than 70% of the hikers since its establishment. Since it was opened in 1995, the Merapoh Trail has been severely trampled, which poses a challenge to the resource integrity and the quality of recreational experiences. The purpose of this study was to assess the resilience of the Merapoh Trail by (i) assessing trail width, trail depth, and composition of vegetation communities in different altitudinal forest zones, (ii) comparing the 1998’s trail width and depth with 2019 based on different altitudinal forest zones, and (iii) examining the relationship between the selected inventory parameters and the degradation of the trail. A total of 321 study stations were established using systematic sampling, and 11 were retrieved from the 1998 and 2000 studies. Based on the result, the trail was widened and deepened as ascending from different attitudinal forest zones with the upper montane forest was recorded with the highest trail width (M=155.11 cm) and trail depth (M=30.18 cm). Vegetation species composition of disturbed and undisturbed areas indicated that the upper montane forest zone had a greater similarity index (CC=0.56) than other attitudinal forest zones and while at the lower montane forest and lowland dipterocarp forest had the lowest vegetation similarity index. The trail width and vegetation similarity index findings suggested that the montane forests had minor vegetation recovery due to the excessive trail widening. Lastly, trail width and depth were significantly associated with the tree canopy cover, slope gradient, and elevation. The results indicated that tree canopy cover, slope gradient, and elevation contributed to the widening and deepening of the Merapoh Trail. These findings provided vital information for managers and park authorities in designing targeted trail monitoring and maintenance programs to minimize the impacts.